WATER INTAKE FACILITIES OF A DERIVATIONAL HYDROELECTRIC POWER STATION - Zhakupova Zhanar; Ardakova Aizhan; Dyussenbiyeva Akerke; Zhaksylyk Karakat (Theoretical Hypotheses and Empirical Results, 2025)
The experience gained in the 1960s and 1990s in the operation of small hydroelectric power plants shows that hydraulic structures, primarily water intake structures, are the most vulnerable part of hydropower nodes. These structures are designed without taking into account significant intra-daily fluctuations in river flow, which are insufficiently studied. The performed analysis of the shortcomings of existing structures of water intake facilities allowed us to develop a new design of water intake content for derivational hydroelectric power plants, for which a patent of the Republic of Kazakhstan was obtained